ESPEN guideline on nutrition and hydration in dementia – Update 2024 - Volkert, Dorothee; Beck, Anne Marie; Faxén-Irving, Gerd; Frühwald, Thomas; Hooper, Lee; Keller, Heather; Porter, Judi; Rothenberg, Elisabet; Suominen, Merja; Wirth, Rainer; Chourdakis, Michael (Clinical Nutrition, 2024)
Background & aims: Dementia is accompanied by a variety of changes that result in an increased risk of malnutrition and low-intake dehydration. This guideline update aims to give evidence-based recommendations for nutritional care of persons with dementia in order to prevent and treat these syndromes. Methods: The previous guideline version was reviewed and expanded in accordance with the standard operating procedure for ESPEN guidelines. Based on a systematic search in three databases, strength of evidence of appropriate literature was graded by use of the SIGN system. The original recommendations were reviewed and reformulated, and new recommendations were added, which all then underwent a consensus process. Results: 40 recommendations for nutritional care of older persons with dementia were developed and agreed, seven at institutional level and 33 at individual level. As a prerequisite for good nutritional care, organizations caring for persons with dementia are recommended to employ sufficient qualified staff and offer attractive food and drinks with choice in a functional and appealing environment. Nutritional care should be based on a written care concept with standardized operating procedures. At the individual level, routine screening for malnutrition and dehydration, nutritional assessment and close monitoring are unquestionable. Oral nutrition may be supported by eliminating potential causes of malnutrition and dehydration, and adequate social and nursing support (including assistance, utensils, training and oral care). Oral nutritional supplements are recommended to improve nutritional status but not to correct cognitive impairment or prevent cognitive decline. Routine use of dementia-specific ONS, ketogenic diet, omega-3 fatty acid supplementation and appetite stimulating agents is not recommended. Enteral and parenteral nutrition and hydration are temporary options in patients with mild or moderate dementia, but not in severe dementia or in the terminal phase of life. In all stages of the disease, supporting food and drink intake and maintaining or improving nutrition and hydration status requires an individualized, comprehensive approach. Due to a lack of appropriate studies, most recommendations are good practice points. Conclusion: Nutritional care should be an integral part of dementia management. Numerous interventions are available that should be implemented in daily practice. Future high-quality studies are needed to clarify the evidence.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Dehydration; Dementia; Guideline; Malnutrition; Nutritional care